OPTIMIZING EARLY CHILDHOOD CRITICAL THINKING SKILLS IN MANAGEMENT STUDIES THROUGH PROJECT-BASED LEARNING MODELS - Iqbali, Muhammad Mushfi El; Rofideh, Luluatur (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to contribute to efforts to improve children's critical thinking skills through the Project Based Learning model. The approach used in this research is qualitative with case study research. This research took place at Bina Anaprasa Kindergarten, Karangayar, Paiton, Probolinggo. The data collection techniques used in this research were observation, documentation and open interviews. Observations were carried out directly observing the learning activities carried out at Bina Anaprasa Kindergarten. Interviews were carried out with the principal and 2 teachers of Bina Anaprasa Kindergarten group B, using the Project Based Learning model showing explorative and probing activities and drawing conclusions from a problem. The Project Based Learning model can also increase children's creativity, so that children's critical thinking skills and creativity can develop well. Through collaboration between schools and families, learning becomes more holistic and supports children's overall development. Schools and families also have a big influence on improving children's critical thinking skills. The implications of this study explain the importance of the role of collaborative education between educational institutions and families in shaping children's critical thinking skills from an early age.